Phytochemical Profile and Biological Activities of Ethylacetate Extract of Peanut (Arachis hypogaea L.) Stems: In-Vitro and In-Silico Studies with Bibliometric Analysis - Idin Sahidin; N. Nohong; Marianti A. Manggau; A. Arfan; W. Wahyuni; Iren Meylani; M. Hajrul Malaka; Nur Syifa Rahmatika; Agung W. M. Yodha; Nur Upik En Masrika; Abdulkadir Kamaluddin; Andini Sundowo; Sofa Fajriah; Rathapon Asasutjarit; Adryan Fristiohady; Rina Maryanti; Nur Indri Rahayu; M. Muktiarni (Indonesian Journal of Science and Technology, 2023)
The utilization of the stems, leaves, and hulls of peanuts (Arachis hypogea) is not as popular as the seeds. This study aimed to investigate the chemical contents and pharmacological activities of A. hypogaea stems in-vitro and in-silico. This study was also completed with bibliometric analysis. The methanol extract (ME) was reextracted by ethylacetate to get ethyl acetate extract (EAE). The chemical contents of EAE were analyzed by phytochemical screening, Liquid Chromatography-Mass Spectroscopy (LC-MS/MS), TPC (Total Phenolic Content), and TFC (Total Flavonoid Content). In-vitro and in-silico studies evaluated antioxidant potency, toxicity, and cytotoxicity toward MCF-7 cell lines. The results showed that EAE contained terpenoids, flavonoids, alkaloids, and phenolics which were supported by LC-MS/MS data. The EAE was categorized as a very strong antioxidant and moderately active in both cytotoxicity and toxicity.